The Implementation of Andragogy Principles by Tutors in The Life Skill - Anwika, Yuka Martlisda; Ayub, Daeng; Jas, Jaspar (Universitas Negeri Padang, 2021)
Adult learning is an effort aimed at self-development carried out by individuals without coercion. In applying the principles of adult learning, tutors are required to be active and adjust to the training participants. In this case, the tutor's role is not only in the training process, but starting from the tutor's performance, managing the learning environment, and evaluating the training process. Tutors have an important role in determining the success of a program. The research method uses descriptive quantitative. The technique used in sampling is purposive sampling. For the total population, the percentage of samples taken in this study was 64.5%. So the number of samples in this study were 142 people. Collecting data using a questionnaire with a Likert scale model. Data analysis techniques using percentages. The results showed that the application of Andragogy Principles by Tutors in the Life Skill Program in PKBM Se-Kabupaten Kampar was in the medium category, meaning that from the application of these andragogical principles it was necessary to make improvements to improve the quality and professionalism of tutors in order to achieve the expected adult learning objectives.Keywords: Andragogy, Life Skill Program